A study on the evidence-based healthcare practice in selected hospital libraries in Metro Manila and the perceived professional competence of hospital medical librarians towards the evolving role of medical librarianship - Roque, Maria Criselda C. (Institute of Library and Information Science, University of the Philippines Diliman, 2003)
During the recent years, the rise of the evidence-based practice appears to fit well for medical librarians. The emergence of Evidence-based medicine (EBM) and Evidence-based healthcare (EBHC) practice in the medical profession has brought to the fore the role of medical librarians in its practice, and has called for a stronger integration of the librarian in the healthcare process. With changes brought about by advancements in technology and proliferation of information in the field of healthcare, a need is created for redefining medical librarianship towards an increasing emphasis in the professional role on issues such as information literacy and other pedagogical aspects related to searching information to assist medical practitioners.